Effectiveness of Using Flipped Learning Strategy in Developing Skills of Programmatic Algorithms Analysis and Design for Eleventh Grade Students in Palestine - Abu Sarah, Abdelrahman Mohammad Sadeq (Journal of Educational and Psychological Sciences, 2020)
This research aims to investigate the effectiveness of using flipped learning strategy in developing skills of programmatic algorithms analysis and design for eleventh grade students/ technology stream in Palestine, in a unit introduced in the Programming and its Development contained in the book of Programming and Automation part 2. The researcher used the one- group- based experimental design in the pretest- posttest. The research sample consisted of (17) eleventh grade students/ technology stream in one of the schools belonging to Qabatia Directorate of Education, in the academic year 2019/2020. A test of "programmatic algorithms analysis and design" skills was prepared. After applying tools and materials of the research, results showed a statistically significant difference between the two grade averages of the students in the pretest and posttest, in favor of the posttest. In addition, flipped learning strategy proved its effectiveness, according to Black- Scholes Equation, in developing skills of programmatic algorithms analysis and design among students. The researcher introduced a number recommendations, including employment of flipped learning strategy in teaching information technology and applied sciences curricula in general, and Programming and Automation in particular, as well as conducting further studies related to this research.
Keywords: Flipped learning strategy; Programmatic Algorithms